2008
DOI: 10.1073/pnas.0712298105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vocalization impairment of Foxp2 (R552H) knockin mice related to speech-language disorder and abnormality of Purkinje cells

Abstract: Previous studies have demonstrated that mutation in the forkhead domain of the forkhead box P2 (FOXP2) protein (R553H) causes speech-language disorders. To further analyze FOXP2 function in speech learning, we generated a knockin (KI) mouse for Foxp2 (R552H) [Foxp2 (R552H)-KI], corresponding to the human FOXP2 (R553H) mutation, by homologous recombination. Homozygous Foxp2 (R552H)-KI mice showed reduced weight, immature development of the cerebellum with incompletely folded folia, Purkinje cells with poor dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
208
3
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(223 citation statements)
references
References 30 publications
10
208
3
2
Order By: Relevance
“…Similar findings are also observed for compound heterozygotes that carry two different non-functional alleles on different gene copies [22 ]. In contrast, heterozygous mice survive to adulthood and appear overtly normal [22 ,24], although some studies have reported mild-to-moderate developmental delay [21,23] which might relate to differences in genomic background [25 ].…”
Section: Wtsupporting
confidence: 63%
See 3 more Smart Citations
“…Similar findings are also observed for compound heterozygotes that carry two different non-functional alleles on different gene copies [22 ]. In contrast, heterozygous mice survive to adulthood and appear overtly normal [22 ,24], although some studies have reported mild-to-moderate developmental delay [21,23] which might relate to differences in genomic background [25 ].…”
Section: Wtsupporting
confidence: 63%
“…However, under conditions of elevated arousal (applying gentle pressure to the tail while lifting the animal) homozygotes do produce ultrasonic calls, albeit of lower intensity [22 ,54]. Pups that are heterozygous for loss-of-function Foxp2 alleles have been described as producing the same number of USIs as wild-types [22 ,54], or a reduced number [21,23]. Where fewer USIs were reported, developmental delay was also observed in the heterozygous state [21,23].…”
Section: What Can Vocalisations Tell Us?mentioning
confidence: 99%
See 2 more Smart Citations
“…32 Sobre la inespecificidad funcional del lenguaje y su significado evolutivo véase Lorenzo (2007). 33 De hecho, otras variantes de FoxP2 han sido puestas en relación con otras habilidades y necesidades de los organismos portadores, como la comunicación ultrasónica que algunas especies de ratones emplean en la comunicación madre-hijo (Shu et al 2005, Fujita et al 2008) o la representación espacial mediante ecolocación de algunas especies de murciélagos (Li et al 2007). A falta de confirmación empírica, podría en todos los casos hablarse de habilidades basadas en la actividad de sistemas de computación homólogos.…”
Section: La Homología Se Confirmaunclassified